The banjo clock - Garthe, Karen, 1949- (New California poetry, 2012)
For Karen Garthe, poetry is a Molotov cocktail. A master of radical invention, Garthe combines brio of conception with linguistic virtuosity, bringing language to new life from the inside at breakneck speed. The Banjo Clock, her second collection, cultivates a luxuriant sensibility even as it interrupts poetic continuity with cuts, ironies, sharp wit, and wild recklessness. In poems that consider poetry itself, Garthe writes about preparing the medium, the ink, "the motion of new utility." She then turns to America's psychic maladies and the need to rehabilitate our democracy, now floundering.